Impact of COVID-19 pandemic on pediatric endoscopy: A multicenter study on behalf of the SIGENP Endoscopy Working Group. Issue 5 (May 2022) - Renzo, Sara; Scarallo, Luca; Antoniello, Luca Maria; Bramuzzo, Matteo; Chiaro, Andrea; Cisarò, Fabio; Contini, Anna Chiara Iolanda; De Angelis, Gian Luigi; De Angelis, Paola; Di Nardo, Giovanni; Felici, Enrico; Iuliano, Silvia; et al.
Abstract : Background: Aim of the present report was to investigate the repercussions of COVID-19 pandemic on the procedural volumes and on the main indications of pediatric digestive endoscopy in Italy. Methods: An online survey was distributed at the beginning of December 2020 to Italian digestive endoscopy centers. Data were collected comparing two selected time intervals: the first from 1st of February 2019 to 30th June 2019 and the second from 1st February 2020 to 30th June 2020. Results: Responses to the survey came from 24 pediatric endoscopy Units. Globally, a reduction of 37.2% was observed between 2019 and 2020 periods with a significant decrease in median number of procedures (111 vs 57, p < 0.001). Both the median number of procedures performed for new diagnoses and those for follow-up purposes significantly decreased in 2020 (63 vs 36, p < 0.001 and 42 vs 21, p < 0.001, respectively). We reported a drastic reduction of procedures performed for suspected Celiac Disease and Functional Gastrointestinal Disorders (55.1% and 58.0%, respectively). Diagnostic endoscopies for suspected IBD decreased of 15.5%, whereas procedures for Mucosal Healing (MH) assessment reduced of 48.3%. Conclusions: Our study provides real-world data outlining the meaningful impact of COVID-19 on pediatric endoscopy practice in Italy.